Replicating Captain Cook's Waistcoat: Exploring the Skills of a Named Embroiderer during the Eighteenth Century. (March 2017) - Larkin, Alison
Abstract : This article discusses a project to replicate an unfinished waistcoat believed to have been embroidered in the late 1770s for Captain James Cook by his wife, Elizabeth. The intention was to explore the techniques of embroidery used during the eighteenth century, and to replicate a garment belonging to a major historical figure. The original waistcoat was embroidered on Tahitian tapa cloth with a linen backing. The embroidery used silk and metallic thread and silver-plated spangles, employing chain stitch, long-and-short stitch and tambouring. The replica was completed using materials closely approximating those available in the 1770s, and constructed using eighteenth-century methods. The project has shed light on the skills and abilities of a known amateur embroiderer of the late eighteenth century, in addition to providing insight into the tastes and physical characteristics of an important historical figure.